PENGEMBANGAN BUKU PINTU AJAIB SEBAGAI MEDIA LAYANAN BIMBINGAN KONSELING PADA SISWA KELAS 6 SEKOLAH DASAR - Qothrun Nada; Nugraha Permana Putra (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The study Development of â€œBuku Pintu Ajaibâ€ as A Medium in Guidance and Counseling Service for Elementary School 6th Graders developed a medium for the implementation of Guidance and Counseling. This study aims to determine the development of the